COVID-19 Patients' Life Events, Emotional Health And Post-Illness Awareness: A Qualitative Study. Issue 2 (3rd April 2022) - Öner, Hatice; Arslantaş, Hülya; Koruklu, Nermin; Sari, Ezgi; Aslan, Rahime
ABSTRACT: Purpose: This study aimed to examine the life events, emotional health and post-illness awareness of COVID-19 patients. We interviewed 25 people who experienced COVID-19. Design: The study was executed in qualitative descriptive design. Methods: The study was conducted with a phenomenological design approach. Data were collected using an in-depth, semi-structured interview method. We interviewed 25 people who experienced COVID-19. Findings: Three themes were identified in the content analysis: "Experiences before COVID-19, " "The active experience of COVID-19, " "Remnants of COVID-19." We found that when participants first heard they tested positive for COVID-19, the anxiety they experienced turned into panic and fear of death as the duration and severity of the symptoms of the disease increased. That uncertainty, as well as the influence of the media, intensified their fears. However, despite the unfavorable conditions, experiencing the disease led to positive awareness in all the participants. Conclusions: We observed that the intensity of the symptoms of COVID-19, the uncertainty of the treatment process, and the attitude of the media were important factors in producing fear and anxiety. Experiencing the illness created an awareness that resulted in the participants' questioning the meaning of life. Clinical Evidence: Within the scope of preventive health services, there is a need for informative programs of education on COVID-19 prevention, coping, and self-improvement that will be useful in reducing the psychological effects of the disease.